Discriminating ferrotoroidic from antiferrotoroidic ground states using a 3d quantum spin sensor - Kieran Hymas; Alessandro Soncini; Kuduva R. Vignesh; Deepanshu Chauhan; Abinash Swain; Sophie L. Benjamin; Dipanti Borah; Maheswaran Shanmugam; Wolfgang Wernsdorfer; Gopalan Rajaraman; Stuart K. Langley; Keith S. Murray (npj Quantum Materials)
Abstract Molecular toroidal states have come to the forefront as candidates for next-generation quantum information devices owing to their bistability and protection from weak, short-range magnetic interactions. The protection offered by these non-magnetic vortex spin states proves to be a double-edged sword as inferring their existence in a molecular system has yet to be achieved through experimental means alone. Here, we investigate the anomalous, sickle-shaped, single-crystal magnetisation profile arising in μ-SQUID measurements of a novel CrDy3 molecule. Theoretical modelling supported by ab initio calculations demonstrates that the weak field CrDy3 spin dynamics is resultant from quantum superposition of the CrIII spin states determined by three competing interactions: (i) the alignment of the CrIII magnetic moment to the external magnetic field, (ii) the zero-field splitting of the CrIII ground quartet, and (iii) coupling to the remnant magnetisation of the toroidal ground state in the Dy3 triangle. If zero-field splitting of the central transition metal ion is quenched, it operates as a quantum spin sensor, which can be exploited to experimentally discriminate between ferrotoroidic and antiferrotoroidic ground states in MDy6 double triangle complexes through electron paramagnetic resonance experiments and single-crystal magnetisation measurements with a restricted field sweeping domain.